Catechol-functionalized adhesive thermogels for wound healing - Teo, Vincent Ting An (Nanyang Technological University, 2023)
Hydrogels have attracted a wide span of attention for wound healing applications owing to their excellent biocompatibility, high water content and ability to retain moisture. However, adhesion to wet interfaces such as biological tissues can be challenging as hydrogels do not possess good adhesive properties. Inspired by mussel’s adhesive proteins, catechol moieties have demonstrated excellent interfacial adhesion in wet environments which can compensate for hydrogels’ deficiency. In this project, catechol moieties have been conjugated with an injectable temperature-responsive hydrogel (Thermogel). The functionalized thermogel allows for dual-crosslinking in response to pH and temperature as well, providing better conformance to wound surfaces through an injectable or potentially sprayable delivery system. Our investigation showed that at a concentration of 7 wt%, the hydrogel exhibited the lowest gelation temperature at 8.6 °C and the amplitude sweep test revealed a yield point of nearly 4000% for the tris-complex. Although more studies are needed for the adhesiveness and mechanical properties of the thermogel, our findings showed promising potential for the product as wound dressing to treat chronic wounds.